When the brain hurts the heart: status epilepticus inducing tako‐tsubo cardiomyopathyth. Issue 3 (17th July 2019) - Giovannini, Giada; Grassi, Laura; Vincenzi, Chiara; Mirandola, Laura; Meletti, Stefano
ABSTRACT: Aims . Tako‐tsubo cardiomyopathy (TTC) is a transient myocardial dysfunction mainly affecting the left ventricle, mimicking an acute coronary syndrome. This condition can be precipitated either by psychological/physical stressful events or by a number of medical conditions among which are seizures and status epilepticus (SE). The evolution is mostly favourable but sometimes TTC can evolve into life‐threatening conditions. Methods . We searched for cases of TTC among all consecutive SE episodes observed at our department during the period 2013–2018. In addition, we searched MEDLINE (accessed through PubMed from inception to August 31, 2018) to identify reports of patients with TTC associated with an SE episode. Results . Three TTC cases among 392 SE episodes were identified. Adding our cases to those previously reported, overall, we identified 45 cases of TTC induced by SE. The majority were females of around 60 years of age experiencing a first episode of SE with prominent motor phenomena, mostly in the context of remote aetiology. The most frequent presenting symptom was mild hypotension but cases with a severe presentation were also reported. The overall evolution was positive in all cases but some severe complications such as pulmonary oedema, cardiogenic shock, ventricular fibrillation, and a giant apical thrombus were also reported (19%). Conclusions . TTC may be a rare potentially life‐threatening consequence of SE. It is frequently unrecognized, and therefore underdiagnosed. Clinicians dealing with SE should be aware of this entity.